Commercial Activity of Agricultural Producers - KULIKOV, I.M.; MINAKOV, I.A. (Journal of Advanced Research in Law and Economics; Vol 11 No 3 (2020): JARLE Volume XI Issue 3(49) Summer 2020DO - 10.14505/jarle.v11.3(49).26, 2020)
The article considers the existing sales system of agricultural products, which does not allow bringing the manufactured products to the consumer promptly and without losses, as well as reveals the features of agricultural production that affect commercial activity, such as dependence of production output on natural and climatic conditions, guaranteed demand, the uneven supply of products to the market, perishable and poorly transportable products, and the concentration of demand in large cities. It is established that the main suppliers of many types of products to the domestic market are agricultural organizations. This is explained by their large production output and a high level of product marketability. The main channel for selling agricultural products is processing enterprises and wholesale trade. It accounts for 77.0% (by wool) to 98.0% (by sugar beet). The sale prices of products vary by distribution channels; this stipulates the different levels of sales profitability. Export is one of the product sales channels; however, it leads to a reduction in the supply of products in the domestic market. The article substantiates the areas for improvement of commercial activity, which include the use of marketing, increasing the competitiveness of products based on improving their quality, creating consumer marketing cooperatives and agro-industrial establishments that combine production, storage, processing, and sale into a single process, participating in fairs, state and regional tenders, using Internet resources, organizing a system of wholesale food markets and logistics centers.